Do early-ending conditional cash transfer programs crowd out school enrollment? - Martin Wiegand (Tinbergen Institute, 2019)
This paper explores how a conditional cash transfer program influences students' schooling decisions when program payments stop in the middle of the school career. To that end, I examine Mexico's Progresa, which covered students only until the end of middle school (at age 15) in its early years. The experimental setup permits to study the program's impact on the probability to continue with high school after middle school. Despite initial randomization, the program itself has likely rendered the respective samples of middle school graduates in the treatment and the control group incomparable. To account for this, I employ a newly developed semiparametric technique that uses a combination of machine learning methods in conjunction with doubly-robust estimation. I find that exposure to Progresa during middle school reduced the probability to transfer to high school by 10 to 14 percentage points. Possible explanations for this effect include parents' loss aversion, motivation crowding, anchoring, and classroom peer effects.
Keywords: I22; I25; O15; J24; D04; D91; C52; 330; education; conditional cash transfer; Progresa; machine learning; doubly-robust estimation; loss aversion; motivation crowding; anchoring; classroom peer effects; Mexico